Even High-Quality CPGs Seldom Include Implementation Strategies - Vasconcelos, Luciana Pereira de; Melo, Daniela Oliveira De; Stein, Airton Tetelbom; Carvalho, Heráclito Barbosa de (Frontiers in Pharmacology, 2021)
Background: Implementation is a key step in ensuring that high-quality clinical practice guideline (CPG) recommendations are followed and have a positive impact. This step must be planned during CPG development. This study aims to inform professionals tasked with developing and implementing CPGs regarding implementation strategies and tools reported in high-quality CPGs for chronic non-communicable diseases (NCDs). Methods: NCD guidelines were selected based on Appraisal of Guideline Research and Evaluation (AGREE) II assessment. CPGs with a score of ≥60% in AGREE II domains 3 (rigor of development), 5 (applicability), and 6 (editorial independence), were considered high quality. The content related to implementation was extracted from CPG full texts and complementary materials. Implementation strategies and tools were assessed and classified using Mazza taxonomy. Results: Twenty high-quality CPGs were selected, most of which were developed by government institutions (16; 80%) with public funding (16; 80%); almost half (9; 45%) addressed the treatment of cardiovascular diseases. The countries with the most high-quality CPGs were the UK (6; 30%) and Colombia (5; 25%). These countries also had the highest average number of strategies, Colombia with 28 (SD = 1) distributed in all levels, and the UK with 15 (SD = 7), concentrating on professional and organizational levels. Although the content of the Colombian CPGs was similar regardless the disease, the CPGs from the UK were specific and contained data-based feedback reports and information on CPG compliance. Implementation strategies most frequently identified were at the professional level, such as distributing reference material (18; 80%) and educating groups of healthcare professionals (18; 80%). At the organizational level, the most frequent strategies involve changes in structure (15; 75%) and service delivery method (13; 65%). Conclusion: Countries with established CPG programs, such as the UK and Colombia, where identified as having the highest number of high-quality CPGs, although CPG implementation content had significant differences. Among high-quality CPGs, the most common implementation strategies were at the professional and organizational levels. There is still room for improvement regarding the implementation strategies report, even among high-quality CPGs, especially concerning monitoring of implementation outcomes and selection of strategies based on relevant implementation barriers.